Os impactos das transferências intergovernamentais nos incentivos orçamentários dos municípios brasileiros - Pedro Jorge Holanda Alves; Jevuks Matheus de Araujo (Instituto de Pesquisa Econômica Aplicada (IPEA), 2021)
– The objective of this work is to analyze the impact of fiscal decentralization on the behavior of Brazilian municipal policy makers. This work uses the first three cutoffs of the transfer rules of the Municipal Participation Fund (FPM) and applies a Discontinuous Regression model (RDD) to capture the effects that affect municipal budget rates during the years 2013 to 2016. The comportment hypotheses is that transfer gains can generate: i) perverse incentives, if the gains are earmarked for personnel and administrative expenses or decrease revenues; or ii) beneficial incentives, if the main gains are spent on education or health. The results found for the estimates of the data panel model is that the increase in exogenous revenue generates a significant increase in spending only in administrative and sports and leisure functions and that the possible channel for this increase in expenses should be aimed at increasing number of employees with commissioned cargo. These results indicate that the transfers generate only perverse incentives.
Keywords: E62; H72; C26; 330; FPM; RDD; municipalities